Validation of mDurance, A Wearable Surface Electromyography System for Muscle Activity Assessment - Molina-Molina, Alejandro; Ruiz-Malagón, Emilio J.; Carrillo-Pérez, Francisco; Roche-Seruendo, Luis E.; Damas, Miguel; Banos, Oresti; García-Pinillos, Felipe (Frontiers in Physiology, 2020)
The mDurance® system is an innovative digital health tool that combines wearable surface electromyography (sEMG), mobile computing and cloud analysis to streamline and automatize the assessment of muscle activity. The tool is particularly devised to support clinicians and sport professionals in their daily routines, as an assessment tool in the prevention, monitoring rehabilitation and training field. This study aimed at determining the validity of the mDurance system for measuring muscle activity by comparing sEMG output with a reference sEMG system, such as Delsys® system. Fifteen participants were tested during isokinetic knee extensions at three different speeds (60, 180 and 300 deg/sec.), for two muscles (rectus femoris [RF] and vastus lateralis [VL]) and two different electrodes locations (proximal and distal placement). The maximum voluntary isometric contraction was carried out for the normalization of the signal, followed by dynamic isokinetic knee extensions for each speed. The sEMG output for both systems was obtained from the raw sEMG signal following mDurance's processing and filtering. Mean, median, first quartile, third quartile and 90th percentile was calculated from the sEMG amplitude signals for each system. The results show an almost perfect ICC relationship for the VL (ICC>0.81) and substantial or almost perfect for the RF (ICC > 0.762). The Bland-Altman plots revealed heteroscedasticity of error for mean, quartile 3 and 90th percentile at 60 and 300 deg/s for RF and at mean and 90th percentile for VL. In conclusion, the results indicate that the mDurance® sEMG system is a valid tool to measure muscle activity during dynamic contractions over a range of speeds. This innovative system provides more time for clinicians (e.g., interpretation patients' pathologies) and sport trainers (e.g., advising athletes), thanks to automatic processing and filtering of the raw sEMG signal and generation of muscle activity reports in real-time.